Distinct patterns of myogenic motor activity identified in isolated human distal colon with high‐resolution manometry. Issue 10 (6th May 2020) - Rosli, Reizal M.; Heitmann, Paul T.; Kumar, Raghu; Hibberd, Tim J.; Costa, Marcello; Wiklendt, Lukasz; Wattchow, David A.; Arkwright, John; de Fontgalland, Dayan; Brookes, Simon J. H.; Spencer, Nick J.; Dinning, Phil G.
Abstract: Background: Colonic high‐resolution manometry (HRM) has been used to reveal discrete, propagating colonic motor patterns. To help determine mechanisms underlying these patterns, we used HRM to record contractile activity in human distal colon ex vivo. Methods: Surgically excised segments of descending (n = 30) or sigmoid colon (n = 4) were immersed in oxygenated Krebs solution at 36°C (n = 34; 16 female; 67.6 ± 12.4 years; length: 24.7 ± 3.5 cm). Contractility was recorded by HRM catheters. After 30 minutes of baseline recording, 0.3 mM lidocaine and/or 1 mM hexamethonium were applied. Ascending neural pathways were activated by electrical field stimulation (EFS; 10 Hz, 0.5 ms, 50 V, 5‐s duration) applied to the anal end before and after drug application. Results: Spontaneous propagating contractions were recorded in all specimens (0.1‐1.5 cycles/minute). Most contractions occurred synchronously across all recording sites. In five specimens, rhythmic antegrade contractions propagated across the full length of the preparation. EFS evoked local contractions at the site of stimulation (latency: 5.5 ± 2.4 seconds) with greater amplitude than spontaneous contractions (EFS; 29.3 ± 26.9 vs 12.1 ± 14.8 mm Hg; P = .02). Synchronous or retrograde propagating motor patterns followed EFS; 71% spanned the entire preparation length. Hexamethonium and lidocaine modestly and only temporarily inhibited spontaneous contractions, whereas TTX increased the frequency of contractile activity while inhibiting EFS‐evoked contractions. Conclusions and Inferences: Our study suggests that the propagated contractions recorded in the organ bath have a myogenic origin which can be regulated by neural input. Once activated at a local site, the contractions do not require the propulsion of fecal content to sustain long‐distance propagation. Abstract : Our study, examines motility patterns in excised sections of human colon. Our findings suggest that the detected propagated contractions have a myogenic origin, yet they can be regulated by neural input.